COMMUNICATIVE APPROACH IN TEACHING FOREIGN LANGUAGE - Mamanazarova Rayhona Nurbek qizi (TADQIQOTLAR, 2025)
Abstract The communicative approach, also known as Communicative Language Teaching (CLT), is one of the most influential methodologies in modern language education. This approach focuses on developing learners’ communicative competence through real-life communication and interactive tasks. The main goal is to help learners use language meaningfully and appropriately rather than merely mastering grammar rules. This paper discusses the theoretical background of CLT, its principles, classroom applications, and its impact on modern foreign language teaching. The research highlights the balance between fluency and accuracy, emphasizing the learner-centered nature of the communicative approach.